2008
DOI: 10.1111/j.1365-2648.2007.04531.x
|View full text |Cite
|
Sign up to set email alerts
|

Existential struggle and self‐reported needs of patients in rehabilitation

Abstract: Title. Existential struggle and self-reported needs of patients in rehabilitation Aim. This paper is a report of a study to increase understanding of patients' experience of rehabilitation and their self-reported needs in that context. Background. Nurses need to be able to recognize patient needs to plan effective and individualized care. Needs-led nursing care is emphasized in the nursing literature, but few studies in rehabilitation have explored needs from the patient's perspective.Method. The sample of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…Negative thoughts had the opposite effect on the participants' recovery. In a qualitative study about people's experience of rehabilitation, Sigurgeirsdottir and Halldorsdottir (2007) found that the participants felt they needed to hold on to faith, hope, and optimism as an essential aspect of adapting to a new self and getting through the difficulties involved with dealing with sudden illness or accident. This is comparable to the participants in our study, who also claimed how joy and humor had positive effects and made daily life easier, a finding also supported by Koch et al (2005).…”
Section: Negativity Versus Positivitymentioning
confidence: 98%
See 4 more Smart Citations
“…Negative thoughts had the opposite effect on the participants' recovery. In a qualitative study about people's experience of rehabilitation, Sigurgeirsdottir and Halldorsdottir (2007) found that the participants felt they needed to hold on to faith, hope, and optimism as an essential aspect of adapting to a new self and getting through the difficulties involved with dealing with sudden illness or accident. This is comparable to the participants in our study, who also claimed how joy and humor had positive effects and made daily life easier, a finding also supported by Koch et al (2005).…”
Section: Negativity Versus Positivitymentioning
confidence: 98%
“…Encounters characterized by uncaring attitudes, lack of counseling and lack of support disempowered them, increased their vulnerability and negatively affected their recovery. It is important in counseling to support and encourage clients to build new ideas about themselves and their possibilities and help them to find new ways Sharf, 2002). This exacerbated vulnerability and need for counseling and support must be illuminated in further studies.…”
Section: Exacerbated Vulnerability In Existential Changesmentioning
confidence: 98%
See 3 more Smart Citations